Analysis of a Marseillevirus Transcriptome Reveals Temporal Gene Expression Profile and Host Transcriptional Shift - Rodrigues, Rodrigo Araújo Lima; Louazani, Amina Cherif; Picorelli, Agnello; Oliveira, Graziele Pereira; Lobo, Francisco Pereira; Colson, Philippe; La Scola, Bernard; Abrahão, Jônatas Santos (Frontiers in Microbiology, 2020)
Marseilleviruses comprise a family of large double-stranded DNA viruses belonging to the proposed order “Megavirales”. These viruses have a circular genome of ~370 kbp, coding hundreds of genes. Over a half of their genes are associated with AT-rich putative promoter motifs, which have been demonstrated to be important for gene regulation. However, the transcriptional profile of Marseilleviruses is currently unknown. Here we used RNA sequencing technology to get a general transcriptional profile of Marseilleviruses. Eight million 75-bp-long nucleotide sequences were robustly mapped to all 457 genes initially predicted for Marseillevirus isolate T19, the prototype strain of the family, and we were able to assemble 359 viral contigs using a genome-guided approach with stringent parameters. These reads were differentially mapped to the genes according to the replicative cycle time point from which they were obtained. Cluster analysis indicated the existence of three main temporal categories of gene expression, early, intermediate and late, which were validated by quantitative reverse transcription polymerase chain reaction assays targeting several genes. Genes belonging to different functional groups exhibited distinct expression levels throughout the infection cycle. We observed that the previously predicted promoter motif, AAATATTT, as well as new predicted motifs, were not specifically related to any of the temporal or functional classes of genes, suggesting that other components are involved in temporally regulating virus transcription. Moreover, the host transcription machinery is heavily altered, and many genes are down regulated, including those related to translation process. This study provides an overview of the transcriptional landscape of Marseilleviruses.